Immunotherapy in Patients With Allergic Asthma and Chronic Allergic Rhinitis: A Retrospective Cohort - Aziza, Seitova; Jassim, Ahmed Mahdi; Mohammed, Sura Akram; Mohammed, Samer Shukur; Nassar, Waleed; Siddiqui, Mohd Faizan (Trends in Immunotherapy, 2025)
Asthma and allergies both cause similar signs and symptoms and often occur together. Evidence for the effectiveness of immunotherapy has rapidly increased in recent years. Several well-designed studies have demonstrated that allergen immunotherapy may prevent the development of asthma in people with allergic rhinitis. The present study aimed to assess the effect of subcutaneous immunotherapy with specific allergens on clinical symptoms, immunological factors, and cytokines in patients with allergic rhinitis and allergic asthma from the Kyrgyz Republic. This retrospective cohort study was conducted on patients with a slight to moderate level of persistent asthma and moderate to severe allergic rhinitis who had been referred to Osh State Clinic in Osh city, Kyrgyz Republic, from March 2000 to February 2025. About 160 atopic patients with allergic rhinitis and asthma were included in the study; confirmed by history, physical examination, and SPT, irrespective of gender. In patients with allergic asthma, 23 (58.97%) patients showed complete symptom improvement, 11 (28.2%) patients showed complete improvement, and 5 (12.82%) patients showed no response to treatment. Compared to previous treatment in the allergic rhinitis group, the cytokine TGFβ was significantly increased (p < 0.001), while the levels of IFN-γ (p = 0.047) and FOXP3 (p = 0.013) were also insignificantly decreased after immunotherapy. This study examined the impact of standard subcutaneous immunotherapy on patients with allergic respiratory diseases. The study also shows that immunotherapy stands as the most effective treatment for asthma and nasal allergies in patients who meet selection criteria, especially when medications do not work.